PMN-MDSC Frequency Discriminates Active Versus Latent Tuberculosis and Could Play a Role in Counteracting the Immune-Mediated Lung Damage in Active Disease - Grassi, Germana; Vanini, Valentina; De Santis, Federica; Romagnoli, Alessandra; Aiello, Alessandra; Casetti, Rita; Cimini, Eleonora; Bordoni, Veronica; Notari, Stefania; Cuzzi, Gilda; Mosti, Silvia; Gualano, Gina; et al. (Frontiers in Immunology, 2021)
Tuberculosis (TB), due to Mycobacterium tuberculosis infection, is still the principal cause of death caused by a single infectious agent. The balance between the bacillus and host defense mechanisms reflects the different manifestations of the pathology. Factors defining this variety are unclear and likely involve both mycobacterial and immunological components. Myeloid derived suppressor cells (MDSC) have been shown to be expanded during TB, but their role in human TB pathogenesis is not clear. We evaluated the frequency of circulating MDSC by flow-cytometry in 19 patients with ac-tive TB, 18 with latent TB infection (LTBI), and 12 healthy donors (HD) as control. Moreover, we investigated the capacity of MDSC to modulate the mycobactericydal activity of monocytes. The association between MDSC level and TB chest X-ray severity score was analyzed. We observed that, unlike active TB, polymorphonuclear (PMN)-MDSC are not expanded in LTBI patients, and, by performing a receiver operating characteristic (ROC) curve analysis, we found that PMN-MDSC frequency supported the discrimination between active disease and LTBI. Interestingly, we observed an association between PMN-MDSC levels and the severity of TB dis-ease evaluated by chest X-ray. Specifically, PMN-MDSC frequency was higher in those classified with a low/mild severity score compared to those classified with a high severity score. Moreover, PMN-MDSC can impact mycobacterial growth by inducing ROS production in Bacillus Calmette et Guerin (BCG)-infected monocytes. This effect was lost when tested with M. tuberculosis (MTB), In conclusion, our data indicate that the elevated frequency of PMN-MDSC in IGRA-positive indi-viduals is associated with active TB. Our findings also pointed out a beneficial role of PMN-MDSC during human active TB, most likely associated with the limitation of inflammation-induced tissue damage.